Variação nictemeral do zooplâncton na baia do Marajó (Ilha de Colares), Pará – Brasil - MORAES, Ana Flávia Martins (2019)
Studies were carried out to evaluate composition, behavior and the small-scale variability of mesozooplankton in a fixed station at Marajó Bay, near Colares island. The bay is characterized by dynamic tidal and oligohaline character. The upper limit of the estuary occurs in this section. Samples were taken according to tidal variation during a diel cycle in December 2009 (rainy season). A 30-cm diameter cylindrical-conical shaped plankton net, 150 μm mesh, and a flowmeter attached was towed on 200 meters-surface. Water samples for temperature, pH, salinity and conductivity were taken simultaneously. Local depth and tides were measured. The tidal patterns exert influence on the salinity (2.2 - 4.3), conductivity (4.28 - 7.77), pH (6.94 - 6.96) and temperature (27.7 °C - 28.9 ºC) of the estuary, which showed low salinity, thermal stability and relative homogeneity. In laboratory analyzes were done in Bogorov chambers under stereoscopic microscope, using using at least three 5 ml aliquots. The community was composed of eight major taxonomic groups and twenty-eight (28) zooplankton taxa. Arthropoda Copepoda was the most abundant group, constituting 56.85% of the total zooplankton, followed by Mollusca and Protista. Among the Crustacea, organisms belonging to Copepoda (Calanoida, Cyclopoida and Harpacticoida), Cirripedia and Malacostraca were registered. Barnacle larvae, adults and copepodites of Oithona bjornbergae, Difflugia sp., and Pseudodiaptomus copepoditos were dominant. In general, the density ranged from 538.3 to 4217.9 org.m-³, with large increases during flooding - H7 (25350.4 org.m-³). Diversity was highest during flooding and spring tides H3, H4, H7 and H8 (0,944, 0.844, 0.884 and 0.896 bits/ind.) and lower during evening ebb and low tides - H5 and H6 (0.490 and 0.501 bits/ind.). The values of evenness (0.637) followed the diversity (0.921 bits.). The taxa of higher frequency of occurrence were barnacle larvae and Pseudodiatomus richardi that occurred in all samples. This mixhaline group seems to reflect the characteristics of this transition estuarine sector. We did not observe a clear diurnal cycle for zooplankton, whose patterns followed the tidal patterns.